Slowly Growing Nodule on the Trunk: Cutaneous Granular Cell Tumor - Özge Gündüz; Gül Erkin; Banu Bilezikçi; Gökhan Adanalı (MDPI AG, 2016)
Granular cell tumor (GCT) is a rare benign neoplasm of the skin that accounts for 0.5% of all soft-tissue tumors. The tumor mostly presents with a symptomatic slowly growing solitary nodule and overlying normal skin; therefore, it is not always considered in the differential diagnosis. Here, we report a 58-year-old female patient who presented with a 4-year history of a slowly growing mass, with a dimension of 5 × 4 cm on her left waist, diagnosed as a GCT at the histopathological examination. The neoplastic cells had centrally located nuclei and granular eosinophilic cytoplasm and stained positively for S100, neuron-specific enolase, and CD68 antibodies. Fifteen months after surgery, the patient still showed no signs of local recurrence or metastases. Although a large diameter is a feature of malignant GCT, our case with cutaneous GCT was localized on the trunk and did not present malignant features clinically and histopathologically.